Review of Literature on Social Movement - Subedi, Tek Nath (Interdisciplinary Journal of Management and Social Sciences, 2021)
Social movement is a broad alliance of people whereby different actors work together to bring change in the existing social order. Sociologist Mario Diani considers informal network, shared beliefs, and collective action as features of social movements. This paper reviews Diani’s concept of social movement along with that of other scholars. Social movements are analyzed from the perspectives of collective behavior, resource mobilization, political process, and new social movement. Scholars strive to differentiate it from sporadic collective human endeavors such as riots, protests, strikes, and shutdowns. Social movements target to overthrow regimes where people’s requirements are not fulfilled, which signal vulnerability of the state to collective action. Also, from a structural perspective, social movements are facilitated by larger international contexts that affect developments at home. The state response leads to new opportunities, and state organizations of old regimes break down and new, revolutionary ones are built.